Research of a thermal mode of machineries and enhancement measures for preparedness of fire rescue vehicles - Kulakovskiy Борис Леонидович; Palubets Сергей Михайлович (Chrezvychaynye situatsii: obrazovanie i nauka, 2006)
This article analyses thermal modes of machineries in fire rescue vehicles. The decision was proposed on how to reduce the arrival time of fire rescue vehicles to a place of emergency, especially in winter time, by maintenance of the demanded thermal mode of the engine and transmission in fire rescue vehicles during expectation time, and also the rapid warm-up of engines at the movement to the place of emergency. The device description is given for regulation of the thermal mode in an underbonnet space of an intemal-combustion engine with remote control.